URGENSI PENGUATAN PEMIKIRAN MODERASI ISLAM DALAM PENDIDIKAN AGAMA DI MADRASAH - Mumuh Muhtarom (Tatar Pasundan : Jurnal Diklat Keagamaan, 2018)
Violence in the name of religion often occurs. Yet when viewed in terms of religious substance, it turns out all religions teach peace, harmony, and goodness. But in fact, why there are acts of violence in the name of religion? Here is where the historical and sociological roots are traced to the rise of violence in the name of religion. Indeed, within a certain period and period, there is often religious violence as an implication of conflict of interest among people who use religious legitimacy. So here is the importance of restoring religious understanding to its original substance values. Apparently, relevant to the religious life of Muslims in Indonesia is to continue to foster and develop Islamic moderation thoughts that are balanced, fair, and mid. Here is the urgency of strengthening the thinking of moderation of Islam in Indonesia as expected by the Ministry of Religious Affairs of the Republic of Indonesia.  Key words: Splinter Flow, Religious Violence, Moderation of Islam, Liberal, Radical.